Description of an architecture for critical distributed and real-time data collection applied to MVEDR - Consigli, Carlos Fernando (2009)
Nowadays, motor vehicle safety has gained a widespread interest. Technological breakthroughs have allowed more efficient system implementations as regards life protection elements for both passengers and pedestrians. Among them, event data recorders (EDRs) can be found.\nIn this paper, we introduce an architecture and hardware simulator to satisfy the Institute of Electrical and Electronics Engineers (IEEE) 1616 standard as well as the Argentinean traffic laws (law 24.449 art. 29 and law 26.363). In order to accomplish this, we built an architecture using Transaction Level Modeling (TLM) methodology, accompanied by a hardware description language called SystemC, proving the vantages of using a high level approach for modeling real time embedded systems.